LITERASI UANG ELEKTRONIK DI KALANGAN MAHASISWA - Puji Lestari; Neni Nofriantika (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2018)
Electronic money or e-money as a means of non-cash payments (electronic payment), is now interested in Indonesian society. Institut Pesantren Mathali'ul Falah (IPMAFA) is a university that has more than 200 students who studied economics focus in particular knowledge of banking Shari'ah. Despite being in the city with minimal transport facilities-based computer line, but the reach of internet facilities were adequate and modern minimarkets nearby, prompting researchers to determine the level of understanding and use of electronic money among the college students. Data collected through interviews with 21 respondents representing 10% students of Islamic banking. By using data analysis techniques Miles and Huberman researchers succeeded in preparing the conclusions of this study. Based on the analysis and discussion, the study concluded that the level of knowledge of students of the Institut Pesantren Mathali'ul Falah regarding electronic money based on the theory Personal Capability Maturity Model (P-CMM), these figures are still at the stage where an individual ever had an experience once or twice, and considers e-payment technology is an essential component for achieving the desire and troubleshooting. While the level of use of electronic money mostly students of the Institute Pesantren Mathali'ul Falah is at a level where an individual has repeatedly using e-payment technology to help with daily activities and has had a recurrence pattern in its use. This means that not all students get to know and use electronic money as a means of non-cash payments.